Chemoprophylaxis with sporozoite immunization in P. knowlesi rhesus monkeys confers protection and elicits sporozoite-specific memory T cells in the liver. - Sathit Pichyangkul; Michele D Spring; Kosol Yongvanitchit; Utaiwan Kum-Arb; Amporn Limsalakpetch; Rawiwan Im-Erbsin; Ratawan Ubalee; Pattaraporn Vanachayangkul; Edmond J Remarque; Evelina Angov; Philip L Smith; David L Saunders (PLoS ONE)
Whole malaria sporozoite vaccine regimens are promising new strategies, and some candidates have demonstrated high rates of durable clinical protection associated with memory T cell responses. Little is known about the anatomical distribution of memory T cells following whole sporozoite vaccines, and immunization of nonhuman primates can be used as a relevant model for humans. We conducted a chemoprophylaxis with sporozoite (CPS) immunization in P. knowlesi rhesus monkeys and challenged via mosquito bites. Half of CPS immunized animals developed complete protection, with a marked delay in parasitemia demonstrated in the other half. Antibody responses to whole sporozoites, CSP, and AMA1, but not CelTOS were detected. Peripheral blood T cell responses to whole sporozoites, but not CSP and AMA1 peptides were observed. Unlike peripheral blood, there was a high frequency of sporozoite-specific memory T cells observed in the liver and bone marrow. Interestingly, sporozoite-specific CD4+ and CD8+ memory T cells in the liver highly expressed chemokine receptors CCR5 and CXCR6, both of which are known for liver sinusoid homing. The majority of liver sporozoite-specific memory T cells expressed CD69, a phenotypic marker of tissue-resident memory (TRM) cells, which are well positioned to rapidly control liver-stage infection. Vaccine strategies that aim to elicit large number of liver TRM cells may efficiently increase the efficacy and durability of response against pre-erythrocytic parasites.